An assessment of genetic variation in vulnerable Borneo Ironwood Eusideroxylon zwageri Teijsm. & Binn. in Sarawak using SSR markers - Siti Fatimah Md Isa; Christina Yong; M Nazre Saleh; Rusea Go (Wildlife Informaton Liaison Development Society, 2021)
Borneo Ironwood Eusideroxylon zwageri Teijsm. & Binn. has high market value for its valuable and durable tmber, which has put it at risk due to illegal logging. This study analyzed E. zwageri genetic variation using four microsatellite markers in populations at Nirwana Rehabilitation Forest (NRF), and Tatau, Sarawak. We found that 20.1% of total genetic variation corresponded to differences between populations, while 79.9% was attributed to differences among individuals from the same population. The Tatau population had lower genetic diversity compared to NRF, and both populations showed depressed heterozygosity indicative of inbreeding. Allelic data were also used to confirm variety level differences proposed by earlier workers, and three informal varieties: zwageri, grandis, and exilis were recognized in the study area. It is expected that the results from this study could serve as baseline data for conservation of this vulnerable species.